Genetic Innovation in Vertebrates: Gypsy Integrase Genes and Other Genes Derived from Transposable Elements - Chalopin, Domitille (Hindawi Publishing Corporation, 2012)
Due to their ability to drive DNA rearrangements and to serve as a source of new coding and regulatory sequences, transposable elements (TEs) are considered as powerful evolutionary agents within genomes. In this paper, we review the mechanism of molecular domestication, which corresponds to the formation of new genes derived from TE sequences. Many genes derived from retroelements and DNA transposons have been identified in mammals and other vertebrates, some of them fulfilling essential functions for the development and survival of their host organisms. We will particularly focus on the evolution and expression of Gypsy integrase (GIN) genes, which have been formed from ancient event(s) of molecular domestication and have evolved differentially in some vertebrate sublineages. What we describe here is probably only the tip of the evolutionary iceberg, and future genome analyses will certainly uncover new TE-derived genes and biological functions driving genetic innovation in vertebrates and other organisms.